Legal Protection of Intellectual Property Rights for Copyright Holders in the Perspective of Community Legal Culture (Journal of Creativity Student, 2020)
In IPR (Intellectual Property Rights) the protection of copyright holders is very important. Intellectual Property Rights (IPR) guarantees legal creators to obtain an advantage from a work that is created. So in this case someone who without permission plagiarizes a work and takes advantage of it will be considered a violation of the law. This is in line with the culture of today's society, with the rapid development of technology, many people are competing to create a work. But sometimes they forget a rule regarding Intellectual Property Rights by plagiarizing other people's work without permission. This makes it a legal violation of Intellectual Property Rights and harms the Copyright holder. The number of plagiarism of other people's work today shows that there is still a low level of public knowledge and law enforcement on copyright in Indonesia. This article will discuss the Protection of Intellectual Property Rights for Copyright holders, where Copyright holders must get legal protection for their works in the midst of the legal culture of society, in which in this case there are still many violations of Intellectual Property Rights.